2017
DOI: 10.1177/1744987117736363
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ views on the impact of mass media on the public perception of nursing and nurse–service user interactions

Abstract: Aims: To examine nurses' views on the impact that mass media has on service users and how this affects nurse/service user interactions. Background: Internationally, the mass media is an important source of health information for the public. Media framing therefore exerts considerable influence on the public's perceptions of healthcare professionals and services. However, it is not known how the reporting of health stories by the media impacts the work of front-line nursing staff. Design: A qualitative interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…Unfortunately, media portrayal of healthcare delivery and many fictional dramatisations, has historically tended to focus on the roles of physicians and nurses, often with outdated gender stereotypes and professional hierarchies (Mitchell, 2019). Nurses viewed media portrayal of their profession predominantly negatively influencing public views and expectations about nurses and contributing to low staff morale (Hoyle et al, 2017). Similarity, negative portrayal of pharmacist was observed in another retrospective observational descriptive study exploring film and television portrayals of pharmacists from 1970 to 2013 (Yanicak et al, 2015).…”
Section: Introductionmentioning
confidence: 57%
“…Unfortunately, media portrayal of healthcare delivery and many fictional dramatisations, has historically tended to focus on the roles of physicians and nurses, often with outdated gender stereotypes and professional hierarchies (Mitchell, 2019). Nurses viewed media portrayal of their profession predominantly negatively influencing public views and expectations about nurses and contributing to low staff morale (Hoyle et al, 2017). Similarity, negative portrayal of pharmacist was observed in another retrospective observational descriptive study exploring film and television portrayals of pharmacists from 1970 to 2013 (Yanicak et al, 2015).…”
Section: Introductionmentioning
confidence: 57%
“…One potential impact of this media framing is on public perceptions of health professionals and health services: research suggests that the media exerts considerable influence on the public's perceptions of healthcare professionals and influences the decisions individuals take about their own and their families' health (Hoyle et al, 2017), though this relationship is complex and needs further attention from audience focused research (Seale, 2003). Balkham and Alderson (2017) suggest that a combination of increased patient expectation, prolonged media interrogation of GPs, continued scrutiny of public sector pay and scandals related to the NHS have brought the integrity of the medical professions into question.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses perceive the media framing of health services to be predominately negative and feel that media reporting can impact negatively on their work (Hoyle et al., 2017). The reporting also does not reflect the wider context and contributing factors toward WPV within the health care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Media reporting shapes and is shaped by public attitudes and interests (Hoyle, Kyle, & Mahoney, 2017; Van Bekkum & Hilton, 2013). This means that how the media frames particular stories related to health care services and professionals can influence the public’s perceptions of those people and services (Hoyle et al., 2017). In his seminal work, Goffman (1974) suggested that people interpret what is going on around them through social and natural frameworks that help shape individuals’ understandings of their social worlds.…”
Section: Introductionmentioning
confidence: 99%